Net profit margin determinants of Islamic subsidiaries of conventional banks in Malaysia - Maisyarah Stapah @ Salleh,; Bayu Taufiq Possumah,; Nizam Ahmat, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study investigates the determinants of Net Profit Margin (NPM) in Malaysia’s Islamic banking system for the period of 2011-2015 by using static panel data analysis. In Malaysia, conventional banks through its Islamic subsidiary banks are dominating the Islamic banking system in terms of total assets, total loans and total deposits. Therefore this paper attempts to investigate the impact of these Islamic subsidiaries of conventional banks towards the NPM. In relation to that, the impact of the conventional parent banks’ Net Interest Margin (NIM) towards its Islamic subsidiary banks’ NPM is also investigated. For the first objective, the displayed results shows positive relationship indicating that the Islamic subsidiaries of conventional banks’ NPM is higher than the full-fledge Islamic banks’ NPM. While the empirical results on the banks’ specific variables suggest that size, risk aversion and operating cost are positively related to NPM. However, credit risk tends to reduce NPM. Besides that, this study also finds that market concentrations and GDP growth will influence NPM in negative ways whilst inflation and Islamic stock market developments will increase NPM. Liquidity however is found insignificant to NPM. As for the second objective, the Islamic subsidiaries of conventional banks’ NPM is observed as being independent from its conventional parent banks’ NIM.